2017
DOI: 10.1534/genetics.116.195438
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous RNAi Pathways Are Required in Neurons for Dauer Formation in Caenorhabditis elegans

Abstract: Animals can adapt to unfavorable environments through changes in physiology or behavior. In the nematode, Caenorhabditis elegans, environmental conditions perceived early in development determine whether the animal enters either the reproductive cycle, or enters into an alternative diapause stage named dauer. Here, we show that endogenous RNAi pathways play a role in dauer formation in crowding (high pheromone), starvation, and high temperature conditions. Disruption of the Mutator proteins or the nuclear Argo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 126 publications
(148 reference statements)
0
21
0
Order By: Relevance
“…To validate our RNAi results, we crossed mutations in dcr-1 , rde-4 , ergo-1 , and hrde-1 into the AMPK mutant background and determined the PD sterility in each of the compound mutants. csr-1 has recently been shown to be required for dauer formation [35] and therefore could not be further characterized in our study. With the exception of dcr-1 , neither the RNAi nor the mutations of these small RNA pathway components affected development or fertility when combined with AMPK mutants under normal growth conditions (S4C and S4D Fig).…”
Section: Resultsmentioning
confidence: 99%
“…To validate our RNAi results, we crossed mutations in dcr-1 , rde-4 , ergo-1 , and hrde-1 into the AMPK mutant background and determined the PD sterility in each of the compound mutants. csr-1 has recently been shown to be required for dauer formation [35] and therefore could not be further characterized in our study. With the exception of dcr-1 , neither the RNAi nor the mutations of these small RNA pathway components affected development or fertility when combined with AMPK mutants under normal growth conditions (S4C and S4D Fig).…”
Section: Resultsmentioning
confidence: 99%
“…elegans Argonaute protein that protects germline-expressed “self” transcripts from RNAi silencing through the organization of active chromatin domains and promotion of sense-oriented RNA polymerase II transcription genome-wide [ 27 32 ]. We previously showed that the CSR-1 RNAi pathway is required in early larval stages for dauer formation in response to starvation and high pheromone conditions and contributes to stable PD/CON changes in the chromatin state and gene expression for a subset of genes in adults [ 11 , 16 ]. In addition, we found 95% of the WT Phe up::WT Stv down seesaw genes overlapped with a previously identified list of genes targeted by CSR-1 in the germ line [ 29 ], suggesting the possibility that CSR-1 may play a prominent role in the regulation of postdauer transcriptional memory as a consequence of environmental history.…”
Section: Resultsmentioning
confidence: 99%
“…elegans double-stranded RNA (dsRNA) generated in neurons and transported to the germ line resulted in transgenerational silencing that is dependent upon the main systemic RNA interference (RNAi) effector, SID-1 (WBGene00004795) [ 15 ]. Our previous work has shown that RNAi-pathways are required in different subsets of neurons for dauer formation in response to distinct environmental stresses, as well as the resulting reproductive plasticity observed between control and postdauer adults [ 11 , 16 ]. These observations raised the intriguing possibility that postdauer animals that experienced different early life stresses retain distinct molecular signatures mediated by non-coding RNA signals.…”
Section: Introductionmentioning
confidence: 99%
“…However, if PTP C119S selectively binds ppp-RNA-similar to PIR-1 C150S-then it remains possible PTP C119S interacts with and promotes viral packaging of cellular or viral ppp-RNAs that function as small-RNA cues that alter host behavior. This possibility is particularly intriguing as a growing number of reports have described the modulation of neural and behavioral activity by small RNAs originating in other tissues (Bharadwaj and Hall, 2017;Cai et al, 2018;Hou et al, 2019;Posner et al, 2019).…”
Section: Pir-1 Exhibits Ppp-rna-specific Binding Activitymentioning
confidence: 99%